The Effect of Intellectual Capital and Corporate Governance on The Performance of Village Credit Institutions - I Gede Cahyadi Putra; Desy Wedasari; Gusti Ayu Putu Wulan Rahmasari (International Journal of Applied Business and International Management, 2020)
The main purpose of this paper is to examine and analyze the effect of intellectual capital and corporate governance on the performance of village credit institutions in Tampaksiring District, Gianyar, Bali. The study population were 32 village credit institutions with 96 respondents. The findings show that there is a positive influence of intellectual capital and corporate governance on the performance of village credit institutions. This indicates that intellectual capital and good corporate governance of village credit institutions, such as human capital, capital structure and relational capital highly will improve the performance of village credit institutions.